SUITABILITY ANALYSIS FOR RICE PRODUCTION IN SAKON NAKHON PROVINCE - Handayanto, Rahmadya Trias; Hirunpongchai, Anussara; Teng, Boravin; Saengmanee, Khanittha; Khangkhun, Nutthapong (JREC (Journal of Electrical and Electronics), 2014)
The factors affecting suitability locations for rice plantation in Sakon Nakhon province will be found using this Geographic Information System (GIS) software by doing manipulation and analysis of spatial data from Thailand government. The data for finding the suitable area for rice plantation are rainfall, elevation, slope, soil depth, soil texture, soil pH, and soil drainage. Based on past result we create factors affected rice production. We analyze the data by reclassify, aggregate, weighted datasets, and overlay technique. Finally, by multiplying these factors, the suitable area for rice plantation is generated. The result shows the map of suitable land use for rice plantation in Sakon Nakhon province which is divided into categories: not suit, marginally suit, moderately suit, and highly suit with percentage from total area 52.5% (5037.94 km2), 36.42% (3488.90 km2), 9.95% (953.47 km2) and 1.05% (100.44 km2) respectively. Key words: GIS, Land Suitability, Rice Production